Analysis of manganese in soils in riparian areas of the Rio Doce State Park after the Fundão dam rupture in Mariana/MG (Research, Society and Development, 2021)
The economic importance of mining activity, as well as its worldwide demand, cause socio-environmental impacts from the process of implementing the activity to the final disposal of the tailings. The rupture of the Fundão dam, located in Mariana-MG, which stored the waste from the processing of iron ore, promoted invaluable environmental damage in the Doce river basin. The present work had as objective to identify the levels of manganese in the soils of the riparian areas in the Doce river State Park after the rupture of the Fundão tailings dam. Six areas of the Doce, Mombaça and Turvo rivers were analyzed, three of which were directly affected by the tailings and three were not affected. The experimental model used was a 3x2x2 factorial: three rivers, two points (upstream and downstream), and two years of collection (2016 and 2017) with four replications. The results showed that the average levels of manganese were higher in the riparian area of ​​the Mombasa river compared to the Doce river, even with only one of its areas affected by the tailings. Between 2016 and 2017, there was a downward trend in manganese values. Of the affected areas, the stretch downstream of the Mombasa river showed higher values ​​when compared to the riparian areas analyzed and affected by the tailings in the Doce river. The areas of the Turvo river, not reached by the tailings, presented the lowest values ​​of manganese concentration. The results indicate an increase in the concentration of manganese in the soils of the riparian areas of the affected rivers, but in a different way.